Successful reduction of urinary catheter placement for correct and incorrect indications after introduction of a prevention bundle - Michela Cipriani; Matthias Schlegel; Marianne Schwark-Bähler; Samuel Henz; Philipp Kohler; Werner C. Albrich (Cambridge University Press, 2024)
The prospective before-after quality improvement study was to assess bundle effectiveness to reduce urinary catheter days and prevent associated complications. All patients with preexisting or new urinary catheters in a regional hospital in Switzerland were included. We showed a reduction of catheter days, incorrect urinary catheter indications, and most strikingly formally correct indications.